Fisioterapia respiratória, pressão intra-abdominal e função renal de pacientes de terapia intensiva - Demarchi, Ana Carolina dos Santos [UNESP] (2016)
Rationale: The presence of Abdominal Hypertension is a frequent condition in ICU patients with a significant impact on mortality. Critical patients have several risk factors for increased abdominal pressure, including mechanical ventilation and positive water balance. A slight increase in abdominal pressure can lead to organ dysfunction, including the Acute Renal Injury, which is a prevalent complication affecting patient in intensive care with a significant impact on mortality. Patients submitted mechanical ventilation are daily undergoing respiratory therapy techniques, however there aren’t studies demonstrating the effects of the techniques used in intensive care on intra-abdominal pressure and renal function in these patients. Objective: To evaluate the influence of different techniques of respiratory physiotherapy on intra-abdominal pressure on critical patients as well as the behavior of renal function and abdominal hemodynamic by implementing these techniques. Patients and Methods: Clinical trial conducted randomized, controlled, crossover, from March 2013 to December 2014 in the Intensive Care Unit at Hospital of São Paulo State University (UNESP-HC) (Botucatu, Brazil). Patients were randomized to receive three sequences of techniques that included: Chest Compression Expiratory, Hyperinflation and Manual Bag-Squeezing. All patients were submitted to three techniques in different consecutive days. Analysis of the technical data were grouped according to the measures carried out and compared among each other. Hemodynamic parameters were evaluated and intra-abdominal pressure before, after and within two hours after the intervention. Renal function was assessed by creatinine clearance, urea clearance and sodium excretion fraction and the intra-abdominal pressure assessed by the original method of Kron at the same moments. Results: We evaluated 31 patients, 17 males with a mean age of 58.1 ± 17.6 years. Intra-abdominal pressure decreased in a statistically significant way with the use of three techniques and two different times that were evaluated. Immediately after the Manual Hyperinflation technique there was a statistically significant increase in glomerular filtration gradient and the Bag-Squeezing technique, there was also an increase in glomerular filtration gradient immediately after and in two hours of intervention. There was an increase of abdominal perfusion pressure immediately at the end and two hours after application of this technique. The urea clearance showed an increase after the implementation of the Bag-Squeezing technique and increased sodium excretion fraction to the technical Manual Hyperinflation and Bag-Squeezing also were observed. Conclusions: Respiratory therapy techniques reduced pressure and improved intra-abdominal hemodynamic in critical care patients. Technical Manual Hyperinflation and Bag-Squeezing increased sodium excretion fraction, and only the last technique increase the clearance of urea. In general, the techniques employed were associated with improvement of the evaluated parameters.